Enhancing Hope and Resilience of Humanity through Religion - Ravichandran, M.V.E. (The International Institute of Knowledge and Management, 2021)
The outbreak of the Covid-19 pandemic has shaken the whole world. This unprecedented pandemic has raised issues in religious beliefs and practices too. People are raising fundamental questions on human suffering, human destiny and God. Religions are expected to provide answers to such questions. This paper tries to identify some of the Christian interpretations to this pandemic and verify their appropriateness. The methodology adopted here is basically qualitative and analytical, and the methods used are document analysis, interviews and focused group discussions. Some view this pandemic as a punishment from God for human evils and others say that it is a sign of the end times. This paper rejects these views as being fundamentalistic in interpretation. Analyzing the sufferings Jesus underwent in his trials and crucifixion, some others propose that the suffering of humanity due to Covid-19 can also turn into an opportunity; a call for conversion; a victory over evil. Therefore this paper proposes that in the face of Covid-19 humanity should rethink the way it deals with nature, the poor and the vulnerable sectors of humanity. The pandemic has reminded humanity of the need to serve others. It has brought out the goodness in many human persons and made them to partake in the struggle against this pandemic with love and dedication. Therefore as Jesus courageously faced the suffering of crucifixion and overcame it, humanity too can overcome this suffering by facing this pandemic with hope and courage, which will improve its resilience against this pandemic.
Keywords: Covid-19; Christianity; Pandemic; Suffering; Hope